Internationalisation in the context of the ‘alternative’ Mittelstand: Investigating the case of a fashion-jewellery Firm - Hoffmann, Marcel H. L. (2014)
The internationalisation of small and medium-sized enterprises (SMEs) is a niche within the academic discipline of international business studies. The consequences of globalisation and liberalisation of markets around the world are confronting many businesses with never before seen challenges. As a result, taking part in the ‘global game’ has become an inevitable response for many firms, in other words forcing them to internationalise. Internationalisation is a phenomenon which describes the increasing involvement of businesses in foreign markets. Within the study of internationalisation, many theories including the Resource Based View (RBV), the Eclectic Paradigm, the Uppsala model and the Interactive Network model have been conceptualised by academics. In the broadest sense however, there is the stage approach to internationalisation, which understands the phenomenon to occur in incremental stages, and the born-global approach, which assumes that businesses are internationally active since their inception. Due to the fact that the two approaches are conceptualised independently from each other, they only allow internationalisation to be investigated in firms residing either in the traditional manufacturing (i.e. through the stage approach) or in the high-tech (i.e. though the born global approach) sector, thereby neglecting firms in other industries. This presents a very significant gap which exists within the academic literature. This Master thesis explores this gap in the internationalisation literature and relates it to the context of Germany’s ‘alternative’ Mittelstand. Renowned as the driver of Germany’s global economic success, the term Mittelstand is used to denote owner-managed SMEs which are not only defined by quantitative terms but also by their social and cultural qualitative characteristics. Many of the businesses which belong to the Mittelstand reside in the traditional manufacturing and high-tech sectors, thereby making the analysis of firms in other – or ‘alternative’ – sectors particularly appealing with regard to the identified gap. The research conducted for this paper mostly concentrates on a qualitative case study conducted in a German fashion jewellery firm, which is representative for the ‘alternative’ Mittelstand. The findings show that the company selected has internationalised for a number of reasons, some which comply with existing theories and some others which do not. Ultimately, the purpose of this thesis is to contribute to a better understanding of the internationalisation of SMEs.